2019
DOI: 10.1038/s41598-019-44157-8
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Microbiota Composition Correlates Between Pap Smear Microscopy and Next Generation Sequencing and Associates to Socioeconomic Status

Abstract: Recent research on vaginal microbiota relies on high throughput sequencing while microscopic methods have a long history in clinical use. We investigated the correspondence between microscopic findings of Pap smears and the vaginal microbiota composition determined by next generation sequencing among 50 asymptomatic women. Both methods produced coherent results regarding the distinction between Lactobacillus -dominant versus mixed microbiota, reassuring gynaecologists for the use of Pap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 61 publications
3
37
0
1
Order By: Relevance
“…Most of the population set was characterized as mestizo ethnicity. Further studies should evaluate a more profound impact of host socioeconomic or educational factors on vaginal microbiota, as previous epidemiological studies in other countries 61 , 66 , 67 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Most of the population set was characterized as mestizo ethnicity. Further studies should evaluate a more profound impact of host socioeconomic or educational factors on vaginal microbiota, as previous epidemiological studies in other countries 61 , 66 , 67 .…”
Section: Discussionmentioning
confidence: 95%
“…In agreement, other studies also revealed that the use of oral contraceptives, intrauterine device, and barrier methods were not related to the risk of vaginal infection 53 , 55 , 56 . It is important to remember that intrinsic and extrinsic factors, such as age, ethnicity, menstruation cycle, lifestyle habits, use of contraceptives and antibiotics may have an impact on the vaginal microbiota 57 61 . Associations between the microbiota plus background variables and clinical outcomes in different stages of a woman’s life are complex, and which intrinsic or external factors drive the community composition it is not fully understood 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional analysis (genome annotation) of the cervicovaginal microbiome whole metagenome shotgun sequencing dataset using Pfam (Protein families) and Gene Ontology (GO) databases generated a set of 98 functional profiles for the 15 cervicovaginal samples with the following ontologies: biological processes (38), cellular components (25) and molecular functions (35). The biological functions which were visualized in the form of a heatmap (Supplementary Figure S2 and Table S9) Table S10).…”
Section: Function Of the Cervicovaginal Microbiomementioning
confidence: 99%
“…However, among women of varying ethnicity and age, and regardless of the number of women under study, this diversity seems to have compositional and structural constraints [13,16,21,22,23,24,25]. Hence, the recognition of five distinct community state types (CSTs): I, II, III, IV and depth assessment of the characteristics (microbial function, composition and structure) of the vaginal ecosystem, its resistome and local immune inflammatory responses are of principal importance in understanding regulation of the cervicovaginal microbiome, vaginal health and disease prevention.…”
Section: Introductionmentioning
confidence: 99%